Implementation of Web Based E-Monitoring for Student Activities Record in SMK Swasta Medan Area 1 - Hizriadi, Ainul; Nasution, Umaya Ramadhani Putri; Purnamasari, Fanindia (Talenta Publisher, 2023)
SMK Medan Area 1 is one of the educational facilities that want to produce the best students to be able to become the best human resources in the future. The school is one of the secondary schools located in the city of Medan, North Sumatra province. The school provides various educational support facilities for its students so that they can learn to the fullest. For the sake of education progress, this Medan Area 1 Vocational School wants to take advantage of the available facilities and infrastructure, one of which is the internet. The school's need to quickly and easily supervise student activities and the curiosity of parents/guardians for information related to their sons and daughters makes a new need to continue to be able to unite all their children's activities at the school. These activities include attendance, tuition payments, notification of grades and violations committed by their sons and daughters. Therefore, a web-based monitoring application is needed to unify student activities that can be seen from anywhere, especially by parents/guardians. aims to provide convenience to teachers, especially counseling guidance (BK) teachers and web-based students in unifying several student activities including attendance, tuition payments, value notifications, and the method used in making applications carried out through five stages, namely: development problems , data collection for system requirements, system analysis and design, system implementation and implementation, and system testing